2004
DOI: 10.1023/b:aseb.0000028887.96873.f3
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Female Sex Work in Tijuana, Mexico

Abstract: Previous research has documented high rates of STDs and increased risk of HIV infection among female sex workers (FSWs) in Mexico; however, little is known about the sexual risk behaviors of this population. The purpose of this study was to explore work history, context of sex work, sexual risk practices, client characteristics, attitudes toward condoms, and potential barriers to condom use in a sample of FSWs in Tijuana, Mexico. Analysis of qualitative data from 25 FSWs revealed that most women entered the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 20 publications
5
121
0
Order By: Relevance
“…34,35 FSW-PWID who earn less income may be more vulnerable overall and deeply entrenched in drug use. Although having a pimp or manager can also exacerbate economic vulnerabilities, previous research with primarily streetbased female sex workers in Tijuana found that only 2.7 % reported having a Bpimp^3 and that these women report maintaining autonomy from men in their work, 36 so we do not think that this is a major factor driving this relationship. On the other hand, having a larger income was protective against relapse, suggesting that interventions targeting women's economic needs (e.g., reducing debt or promoting savings through microfinance programs or providing vocational training) could help women to stop injecting drugs and avoid relapse.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…34,35 FSW-PWID who earn less income may be more vulnerable overall and deeply entrenched in drug use. Although having a pimp or manager can also exacerbate economic vulnerabilities, previous research with primarily streetbased female sex workers in Tijuana found that only 2.7 % reported having a Bpimp^3 and that these women report maintaining autonomy from men in their work, 36 so we do not think that this is a major factor driving this relationship. On the other hand, having a larger income was protective against relapse, suggesting that interventions targeting women's economic needs (e.g., reducing debt or promoting savings through microfinance programs or providing vocational training) could help women to stop injecting drugs and avoid relapse.…”
Section: Discussionmentioning
confidence: 59%
“…32,44,45 For FSW at the US-Mexico border, a large majority have dependent children and financial responsibilities for them has frequently been cited as a key reason for entering sex work. 36,48 Previous studies by our group suggest, however, that FSW-PWID are less likely to report living with their children than other FSWs, 19, 49 perhaps because they have been apprehended by child welfare agencies. The provision of child care and support for child custody may then be an important motivator for women to enter and stay in MMTPs or other harm reduction programs.…”
Section: Discussionmentioning
confidence: 77%
“…Similar increases were seen following the Great Depression in the United States (Allen, 2004) and during the economic turmoil in the former USSR in the 1990s (Aral et al, 2003;Atlani et al, 2000). Interview or questionnaire-based studies …nd a similar pattern -when asked, a signi…cant fraction of women report that the reason that they entered sex work was …nancial distress or hardship (see Bucardo et al, 2004 for a study in Mexico; and Robinson and Yeh, 2011b for evidence from Kenya). These studies all focus on the extensive margin of sex work (entry into the profession).…”
Section: Introductionmentioning
confidence: 76%
“…15 However, these e¤ects are relatively small compared to the e¤ect of the Thus we …nd surprisingly little di¤erence in smoothing ability across individuals overall. 16 This speaks to the nature of the crisis, a fundamental political crisis which was felt throughout Kenya, making interpersonal risk-coping di¢ cult. Thus, it does not appear to be the case that certain individuals su¤ered because they were isolated from social networks.…”
Section: Heterogeneity In E¤ects and Responsesmentioning
confidence: 99%
“…Although some FSWs in these cities are relatively high income earners, most are from lower socioeconomic strata. Most enter prostitution out of economic necessity (Bucardo et al, 2004); for example, due to a failed relationship or intolerable working conditions in maquiladoras (Grossman et al, 1985), (i.e., assembly plants that use their low labor costs to attract manufacturing contracts from foreign firms). Factors related to their mobility, such as extreme poverty and low social support, may heighten their vulnerability to HIV/STIs (Fernandez, 1998, Rangel et al, 2006.…”
Section: Introductionmentioning
confidence: 99%